Assessing Climate Driven Malaria Variability in Ghana Using a Regional Scale Dynamical Model - Asare, Ernest O.; Amekudzi, Leonard K. (Climate, 2019)
An article published by Climate 2017, 5, 20; doi:10.3390/cli5010020